Bacterial Isolatesfrom the Genital Aspirates of Cyclic, Acyclic, Endometritic and Pregnant Buffaloes - Patel, Binal R; Panchal, MT; Dhami, AJ; Mathakiya, RA; Bhanderi, BB (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was carried out on 50 vaginal secretions/aspirates/discharge samples collected aseptically using syringe and pipette method from infertile (anestrus; endometritic, n = 6 each) buffaloes of villages nearby Anand and healthy cyclic (n = 5; proestus, estrus, metestrus, diestrus) as well as 3, 6 and 9 month pregnant (n = 6 each) buffaloes of University farm to identify the vaginal microorganisms based on routine cultural examination. In all 117 bacterial isolates were recovered from all 50 vaginal samples (100 %) of 35 buffaloes during different physio-pathological status. The bacteria isolated from vaginal mucus/aspirates of buffaloes during the follicular phase comprised Corynebacterium spp. asthe most predominant isolate (28.57%) followed by E. coli, Bacillus Spp., Staphylococcus spp., Streptococcus spp., Salmonella spp., Proteus spp., and vaginal yeast, whereas during the luteal phase, the most predominant bacteria were E. coli (23.33%) followed by Corynebacterium spp., Bacillus spp., Staphylococcus spp., Streptococcus spp., and Klebsiella spp. In acyclic buffaloes, the most predominant bacteria isolated were Corynebacterium spp. (21.43%) Bacillus spp., Micrococcus spp., Pseudomonas, Staphylococcus spp., Streptococcus spp., E. coli and Salmonella spp., whereas the endometritic buffaloes evinced the most predominant bacterial isolates as Corynebacterium spp. and E. coli (20.00% each) followed by Bacillus spp., Salmonella, Proteus spp., Staphylococcus spp., Streptococcus spp., and Klebsiella spp. The major bacteria isolated during the entire period of pregnancy were E. coli, Micrococcus, Corynbacterium Spp., Bacillus spp., Staphylococcus spp. and Proteus. This study concludes rich bacterial diversity in the vagina of buffaloes during different physio-pathological status.